1 Mobile Health Apps in Burns: Where Is the Quality Control?. (28th February 2022) - Patel, B.; Edwards, T.; Schrire, T.; Senn, S.
Abstract: Aim: High quality mobile health applications (mhealth apps) have the potential to enhance the prevention, diagnosis, and treatment of burns. The primary aim of this study was to evaluate whether the quality of mhealth apps for burns care is being adequately assessed. The secondary aim was to determine whether these apps meet UK regulatory standards. Method: We searched AMED, BNI, CINAHL, Cochrane library, Embase, Emcare, Medline and PsychInfo to identify studies assessing mhealth app quality for burns. The PRISMA reporting guideline was adhered to. Two independent reviewers screened s to identify relevant studies. We analysed whether seven established domains of mhealth app quality were assessed: design, information/content, usability, functionality, ethical issues, security/privacy, and user-perceived value. Results: Of the 28 included studies, none assessed all seven domains of quality. Design was assessed in 4/28 studies; information/content in 26/28 studies; usability in 12/28 studies; functionality in 10/28 studies; ethical issues were never assessed in any studies; security/privacy was not assessed; subjective assessment was made in 9/28 studies. 17/28 studies included apps that met the definition of 'medical device' according to MHRA guidance, yet only one app was appropriately certified with the UK Conformity Assessed (UKCA) mark. Conclusions: The quality of mHealth apps for burns are not being adequately assessed. The majority of apps should be considered medical devices according to UK standards, but only one was appropriately certified. Regulatory bodies should support mhealth app developers, so as to improve quality control whilst simultaneously fostering innovation.